If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 11 = 41 Reorder the terms: 11 + 3x = 41 Solving 11 + 3x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3x = 41 + -11 Combine like terms: 11 + -11 = 0 0 + 3x = 41 + -11 3x = 41 + -11 Combine like terms: 41 + -11 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| 9x-1=6x+26 | | 2(3x+5)=3(2x+3) | | 6x+10=6x+9 | | 3x-5=-99-10x | | -3-3x=4x+9 | | 75-5x=12-8x | | x/3+3=5/6+2 | | x(3x-11)=44 | | ln(y)+(1/3)*ln(x)=c | | 2X+5=105 | | 4x+6=8x-34 | | 1/4+1/12x=2/3 | | =60x^3-240x^2+240x | | 12x-20x^2=0 | | 8y+7x=8 | | x^3+64=(x+a)(x^2+bx+c) | | 7c=-28 | | y+1=-10/7(x+8) | | -3x+15=x-1 | | 7(t-2)+8t=5(3t+3)-9 | | 3a^3b^3-9a^2b^4=0 | | log(x-2)-log(4-x)=1-log(13-x) | | 8x-12x^2=0 | | 2w^2+5w-44=0 | | 0.3(x+30)+1.5x=90 | | 10x+2y=03x+5y=33 | | 3a^3b^3-9a^2b^4= | | 2x-7=14-5x | | (4x-5)+(9x+2)=(4-6x)-(7x+8) | | 10x+2y=0 | | 5e^3x=19 | | 3+7p-2=9p+26-7p |